Exiting Prostitution - Matthews, R. author. aut Link
IX, 162 p.
Keywords: How people move from deviant to conventional lifestyles is an issue that has attracted considerable interest over the past few years. However, much of this work has focused on men desisting from crime. This book provides one of the first examinations of desistance which is centred on women and, more specifically, how they exit prostitution.